Two new species and one new subspecies of Begonia (Begoniaceae) from Southeast Sulawesi, Sulawesi, Indonesia - Deden Girmansyah (REINWARDTIA, 2009)
Two new species and one new subspecies, of Begonia are described from the Mekongga Mountains in Southeast Sulawesi: Begonia mekonggensis Girmansyah & Wiriadinata, Begonia watuwilensis Girmansyah, and Begonia aptera Blume subsp. hirtissima Girmansyah & D.C.Thomas,. Begonia mekonggensis and Begonia watuwilensis belong to Begonia section Petermannia. Both species have characters which are very unusual amongst species in this section. Begonia mekonggensis is dioecious, and Begonia watuwilensis exhibits protandrous inflorescences with basal male flowers and several distal female flowers. Begonia aptera Blume subsp. hirtissima belongs to Begonia section Sphenanthera.